Ovarian Torsion in Pregnancy: A Case Report - Albadrani, Yasmeen Hassan (Journal of medical and pharmaceutical sciences, 2024)
The ovary’s Torsion is the adnexa’s total or partial rotation around its vascular axis or pedicle. Although the exact etiology is unknown, common predisposing factors include a moderately sized cyst, free mobility, and a long pedicle. Torsion of ovarian tumours predominantly occurs in the reproductive age group. Most cases are presented in pregnant women (22.7%) compared to non-pregnant women (6.1%). Here, we report a case of ovarian torsion in pregnancy. Ovarian torsion is an urgent gynaecological condition that can occur during pregnancy. Surgical intervention should be considered in developing adnexal torsion regardless of gestational age.